Evaluation of Water Resources in the Administrative Area of Jableh - عبدالرحمن عباس; أحمد لميس (Latakia University Journal -Engineering Sciences Series, 2021)
Syria is located in the semi-arid region and suffers from limited water resources, especially since these water resources are under great and increasing pressures due to the large population increase. Studies have also indicated that any increase in temperature and a decrease in rainfall as result of climate changes will lead to a signiticant exacerbation of the difficulties associated with securing water. Most government policies and five-year plans have been directly or indirectly linked to water resources from residential, agricultural and industrial projects. The research aims to develop a mathematical model for water resoureces in the Jableh area by using the Weap21program,which is based on the idea of water balance, considering 2012 as the base year, where data related to dams and springs in the Jableh area, which represent used for the full needs of drinking and irrigation, were entered .And trade, tourism and industry, the waste percentage was calculated. And the realized and unrealized need and coverage rate, the causes of waste were identified, and the research showed the importance of the Assin spring for the jableh region,as it meets most of the needs the per capita share is reduced to less than100liter per day, and the inability to secure irrigation water in some year. Recommendations included maintaining the drinking water network to reduce the rate of waste and find a solution to secure water irrigation.